THE INFLUENCE OF RECRUITMENT AND SELECTION PROCESS ON TECHNICAL EMPLOYEE PERFORMANCE IN PT. TELKOM AKSES NORTH SURABAYA - Baruno, Agustiawan Djoko; Permatasari, Leny Novita (Ekspektra : Jurnal Bisnis dan Manajemen, 2020)
This research  aims to  analyze the influence of the process of recruitment and  selection simultaneously as well as partially against employee performance support. In this study using a type of associative methods and quantitative data primary data sources by using the instrument of the questionnaire. The population in this research is the employee technician  PT. Telkom Akses Surabaya Utara as many as 56 respondents.Sampling technique used was saturated samples or often called as well with a sample of the total. Analytical techniques used in this research is the Partial Least Square (PLS) includes test convergen validity, discriminan validity, composite realibility, cronch alpha, R- square, simulan test (test F) and partial test (test T). The results of the analysis explains that the process of recruitment and selection effect simultaneously against the performance of the employee, this is indicated by the value of the count of 40.991 F is greater than F table 4.02 and significance value (S ig) 0.000 smaller than 0.05 and the process of recruitment of influential partially against the performance of the employee, this is shown by the value T calculate of 3.024 is greater than 1.96 table T and value its significance (P values) 0.003 smaller than 0.05. As well as a selection of influential partially against the performance of the employee, this is shown by the value T calculate of 2.856 is greater than 1.96 table T and value its significance (P values) 0.004 smaller than 0.05